“Early” Virus-Specific RNA May Contain Information Necessary for Chromosome Replication and Mitosis Induced by Simian Virus 40 - May, Evelyne (1973)
Simian Virus 40 (SV40) induces in “contact-inhibited” tissue culture cells of mouse kidney an abortive infection that leads to the appearance of intra-nuclear SV40-specific tumor (T-) antigen, followed by replication of the mouse-cell chromatin and mitosis, while no viral progeny DNA or capsid protein is produced. Synthesis of “early” SV40-specific RNA (“19S RNA”) begins a few hours before the appearance of T-antigen and appears to be switched off after the onset of chromatin replication. As the most simple working hypothesis that can account for the experimental results available, we assume that early SV40 RNA contains information necessary for production of T-antigen and that this antigen (or an unknown early virus-specific function that would simply parallel the appearance of T-antigen) activates or de-inhibits a cellular regulatory element that governs chromosome replication and mitosis. The experimental results agree with the idea that SV40 acts primarily as a mitogen.